Invasion Acacia tree species affect instream litter decomposition through changes in water nitrogen concentration and litter characteristics - Pereira, Ana (2021)
Non-native nitrogen-fixing Acacia species have been invading riparian ecosystems worldwide, potentially threatening stream communities that strongly depend on allochthonous litter. We examined the effects of the invasion of native deciduous temperate forests by Acacia species on litter decomposition and associated fungal decomposers in streams. Litter of native (Alnus glutinosa and Quercus robur) and invasive (Acacia melanoxylon) species were enclosed in fine-mesh bags and immersed in three native and three invaded streams, for 14–98 days. Litter decomposition rates, fungal biomass, and aquatic hyphomycete sporulation rates were higher in invaded than in native streams, likely due to the higher water nitrogen concentration found in invaded streams. Alnus glutinosa litter had higher aquatic hyphomycete sporulation rates and species richness, and higher decomposition rates, probably because they were soft and nitrogen rich. Quercus robur litter also had high aquatic hyphomycete sporulation rates but lower decomposition rates than Al. glutinosa, probably due to high polyphenol concentration and carbon:nitrogen ratio. Acacia melanoxylon litter had lower aquatic hyphomycete sporulation rates and species richness, and lower decomposition rates, most likely because it was very tough. Thus, litter decomposition rates varied in the order: Al. glutinosa > Q. robur > Ac. melanoxylon. The aquatic hyphomycete community structure strongly differed between native and invaded streams, and among litter species, suggesting that microbes were sensitive to water nitrogen concentration and litter characteristics. Overall, increases in water nitrogen concentration and alterations in litter characteristics promoted by the invasion of native riparian forests by Acacia species may affect the activity and community structure of microbial decomposers, and instream litter decomposition, thus altering the functioning of stream ecosystems